MODULAR ROBOT DESIGN AND APPLICATION FOR CHILDREN'S DEVELOPMENT IN MECHATRONICS AND AUTOMATION - (:unkn) unknown (INT ORGANIZATION CENTER ACAD RESEARCH, 2017)
The effect of activity sets in the education of primary students in science class was examined using modular automation sets in this study. It is aimed to understand their scientific process skills and motivation towards other integrated technologies. The study group of this research consists of the 4th grade students of a private school on the Anatolian side of Istanbul. Students were given an activity to carry out within the scope of this research by using these automation sets which were procured by the school. A model from the set was designed by the students and the students were requested to make improvements on this model with the guidance and directions of their teacher. The changed parts in the improved model were designed and printed out from a 3D printer. A touch sensor was installed on the finished model and the program software was reconstructed. Finally the students in the study group were subjected to a comprehension test and the results were evaluated. The result of the study shows that students have positive inclination towards building and programming their own designs. Also the use of visual blocks in the system software has shown an increase in student attention and it's been observed that this contributes to easier understanding of the software by the students.
Keywords: Modular toy; Mechatronic activity; Modular application set; 3D Printer; Visual programming